Characterization of hard candy from Roselle (Hibiscus sabdariffa). - Encio, Quinzelle Ann Elesterio
Hard candy was processed with varying concentration of Roselle powder namely Formulation 1 (3%), Formulation 2 (5%) and Formulation 3 (7%). Using a pH differential method, the anthocyanin content of the three formulations, expressed as cyanidin-3-glucoside were 16.38 mgL-1 (F1), 45.55 mgL-1 (F2) and 52.97 mgL-1 (F3). While the radical scavenging activity (RSA), expressed in percent reduction of the radical DPPH were 64.14%, 73.03% and 91.77% for F1, F2 and F3 respectively. Among formulations, one-way ANOVA at P-value 0.05 indicated significant differences in total anthocyanin and RSA. The total anthocyanin and %RSA of the roselle candy were strongly correlated at P-value o.05, indicating that the antioxidant activity of roselle candy is primarily attributed to anthocyanin. Kramer?s Rank Sum Test showed F3 as the most preferred F1 and F3 were similarly preferred but based on least average total rank and functional value, F3 was selected as the most preferred formulation. Kruskal-Wallis test for general acceptability showed no significant difference among formulations at 5% level of significance. The general acceptability rating for Formulation 1 and 3 were ?like moderately? while formulation 2 was ?like slightly?. The most preferred formulation (F3) has a pH of 2.9, water activity of 0.349, 1.48% titratable acidity and 74°B TSS. The physico-chemical characteristics of the candy were indications of a stable product, not prone to yeast and mold growth. The MPF of roselle candy was described as dark red in color, slightly sour taste, highly opaque solid very hard texture. Consumer testing showed that 65.56% liked the product very much, 24.44% liked the product moderately, 3.33% liked the candy slightly, 2.22% of the respondents neither liked nor disliked the product, 2.22% disliked it slightly and 2.22% disliked the product very much.